Penerapan Ilmu Tajwid dalam Pembelajaran Al-Qur'an untuk Mengembangkan Kemampuan membaca Al-Qur'an pada Siswa Kelas AtasSD Muhammadiyah 14 Surakarta - Alfianto, Ervin; , Drs. Suwarno, S.H., M.Pd (2017)
Quran learning is a learning that exists inSD Muhammadiyah, because SD Muhammadiyahis different from other public schools. SDMuhammadiyah implements integral education system, which combines religious sciences with other sciences. The purpose of this study was to get information about the implementation of Quran learning in term of tajwid science implementationinto reading the Quran to develop the ability to read the Quran on the students of high classat SD Muhammadiyah14 Surakarta. The result of this study indicates that Quran learning inSD Muhammadiyah14 Surakarta for tajwid scienceimplementationinhigh class are using different materials for each class, because it has regulated in the curriculum of primary and secondary educational assembly. Religion teacher as the implementerof Quran learning process, when conducting Quran learning the teacher usually teaches the material which exsists in one of basic competences and used for two meetings in order to get maximum results. In the first meeting the teacher puts more emphasis into the understanding of tajwid science material and for the second meeting the teacher will conduct more practices for reading the Quran in order to make the ability to read the Quran on the students continues to grow. Keywords: Quran learning, Tajwid science, Quran reading ability